Digital inclusion of the Orang Asli of Peninsular Malaysia: Remote virtual mechanism for usability of telecentres amongst indigenous peoples - Poline, Bala; Tan, Chong Eng (Electronic Journal of Information Systems in Developing Countries (EJISDC), 2021)
Over the last decades, researchers and development practitioners have been experimenting with models, frameworks and devises to meet the needs of diverse users of information communication technologies. Turning to an ICT‐based community development known as the Telecentre Programme amongst Orang Asli, an indigenous people groups in Peninsular Malaysia, this paper describes why a remote virtual management devise was invented to encounter challenges related to rugged terrain constraints, which would have directly impacted the planning and the execution of programmes designed at the telecentres. This paper argues as a technological solution, the virtual remote management system has powered an ecosystem, which shored up the digital inclusion of the indigenous communities and in the process enabled the enhancement of local informational capabilities. To this end, it reduced their technological dependency on outsiders leading to the usability and sustainability of the telecentre for local capacity building and socioeconomic benefits for the disadvantage communities.